Crystal and magnetic structures of 2H BaMnO3 - Cussen, E; Battle, P (2000)
The crystal structure of the 2H perovskite BaMnO3 has been refined from neutron powder diffraction data collected at room temperature and 80 and 1.7 K. The structure consists of chains of face-sharing MnO6 octahedra, separated by Ba2+ cations. At room temperature, a = 5.6991(2), c = 4.8148(2) Å, space group P63/mmc. At 80 K, a = 9.8467(1), c = 4.8075(1) Å, space group P63cm. The structural phase transition introduces a displacement of neighboring chains and reduces the coordination number of Ba2+. Long-range antiferromagnetic ordering is apparent below T(N) = 59(2) K, with a magnetic moment of 1.31(5) μ(B) per Mn4+ cation at 1.7 K. Neighboring spins within each chain are antiferromagnetically coupled and lie in a plane perpendicular to [001]. The spin directions associated with the chains at (1/3, 2/3, z) and (2/3, 1/3, z) are rotated by ±120°with respect to that of the chain at (0, 0, z).